2012
DOI: 10.1038/onc.2012.173
|View full text |Cite|
|
Sign up to set email alerts
|

Context-dependent differences in miR-10b breast oncogenesis can be targeted for the prevention and arrest of lymph node metastasis

Abstract: Metastases, and not the primary tumor from which they originate, are the main reason for mortality from carcinoma. Although the molecular mechanisms behind metastasis are poorly understood, it is clear that epigenetic dysregulation at the level of microRNA expression is a key characteristic of the metastatic process that can be exploited for therapy. Here, we describe an miRNA-targeted therapeutic approach for the prevention and arrest of lymph node metastasis. Therapy relies on the inhibition of the pro-metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
128
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(136 citation statements)
references
References 26 publications
(40 reference statements)
8
128
0
Order By: Relevance
“…MN-antimiR10b nanoparticles were also capable of inhibiting migration and proliferation of tumor cells in lymph node metastatic tumors. In vivo MRI revealed that the nanoparticles are effectively targeted to the tumor site (Yigit et al, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…MN-antimiR10b nanoparticles were also capable of inhibiting migration and proliferation of tumor cells in lymph node metastatic tumors. In vivo MRI revealed that the nanoparticles are effectively targeted to the tumor site (Yigit et al, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The model used here is based on dextran-coated iron oxide nanoparticles(MN) as delivery vehicles and LNA-modified antisense oligonucleotides as direct miRNA inhibitors. 11 …”
Section: Discussionmentioning
confidence: 99%
“…10 Recently, using a nanodrug specific for the pro-metastatic miR-10b 7 , we demonstrated effective prevention and arrest of lymph node metastasis in a murine model of breast cancer. 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Several delivery strategies have been studied to deliver miRNAs, such as silica nanoparticles, 23 ultrasmall magnetic nanoparticles, 24 liposomes, 25 and exosomes. 26 Among various delivery systems, polyurethane (PU) is a polymer composed of organic units joined by carbamate (urethane) links.…”
mentioning
confidence: 99%